Recent advances - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In 1996 CTA drew up a five-year Mid-Term Plan (MTP) to help the Centre re-orient its activities to reflect the changing needs of its ACP partners. By the end of 1999, CTA s programme had expanded considerably, comprising 228 separate projects,...